2020
DOI: 10.1111/eva.13027
|View full text |Cite
|
Sign up to set email alerts
|

A continuously changing selective context on microbial communities associated with fish, from egg to fork

Abstract: Fast increase of fish aquaculture production to meet consumer demands is accompanied by important ecological concerns such as disease outbreaks. Meanwhile, food waste is an important concern with fish products since they are highly perishable. Recent aquaculture and fish product microbiology, and more recently, microbiota research, paved the way to a highly integrated approach to understand complex relationships between host fish, product and their associated microbial communities at health/disease and preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 268 publications
(358 reference statements)
1
14
0
Order By: Relevance
“…Overall, results from other vertebrate model species (e.g. mouse, human, zebrafish, stickleback) showed that there are multiple ways in which the dialogue between two eukaryotic hosts can involve microbial communities: host–microbiota interactions, microbiota–microbiota interactions, and host–host interactions (reviewed in [ 39 , 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, results from other vertebrate model species (e.g. mouse, human, zebrafish, stickleback) showed that there are multiple ways in which the dialogue between two eukaryotic hosts can involve microbial communities: host–microbiota interactions, microbiota–microbiota interactions, and host–host interactions (reviewed in [ 39 , 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbial communities of fish shift with host development and living environments ( Yan et al, 2016 ; Lokesh et al, 2018 ; Derome and Filteau, 2020 ). Water is a living matrix in which many microbes reside, and it serves as a source for the fish gut microbiome ( Sun et al, 2019 ; Sehnal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the gut microbial community develops continuously during early life (yolk sac larvae–fry–fingerling) in a relatively harsh host–microbiome interaction environment under commercial aquaculture practices [ 8 ]. These pioneering microbes are particularly influential in the early life stage of the host, through fine tuning of host epigenetic patterns, and might therefore have a long term effect on the overall fitness of the host [ 9 11 ]. Therefore, the early environment may define the development and long-term fitness of the host via inoculation of the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%